2020
DOI: 10.1542/peds.2020-0115
|View full text |Cite
|
Sign up to set email alerts
|

Family Well-being in Grandparent- Versus Parent-Headed Households

Abstract: BACKGROUND AND OBJECTIVES: Little is known about the 2% of US children being raised by their grandparents. We sought to characterize and compare grandparent-and parent-headed households with respect to adverse childhood experiences (ACEs), child temperament, attention-deficit/hyperactivity disorder (ADHD), and caregiver aggravation and coping. METHODS: Using a combined data set of children ages 3 to 17 from the 2016, 2017, and 2018 National Survey of Children's Health, we applied survey regression procedures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…The death of custodial grandparents may compound the family adversities that led to the child being cared for by grandparents, rather than parents. Children living in grandparent-headed, versus parent-headed homes, are more likely to have experienced other ACEs, such as incarceration of a parent, separation or divorce, parental alcohol/drug abuse or mental health problems, or domestic violence 45 . Thus, the death of a grandparent often adds another level of adversity that further increases the likelihood of long-term health and social consequences of ACEs 36 .…”
Section: States With Highest Disparities For Children In Covid-19-associated Death Of Caregiversmentioning
confidence: 99%
“…The death of custodial grandparents may compound the family adversities that led to the child being cared for by grandparents, rather than parents. Children living in grandparent-headed, versus parent-headed homes, are more likely to have experienced other ACEs, such as incarceration of a parent, separation or divorce, parental alcohol/drug abuse or mental health problems, or domestic violence 45 . Thus, the death of a grandparent often adds another level of adversity that further increases the likelihood of long-term health and social consequences of ACEs 36 .…”
Section: States With Highest Disparities For Children In Covid-19-associated Death Of Caregiversmentioning
confidence: 99%
“…internalising and externalising problems) between grandparent-headed households and parentheaded households. Rapoport et al (2020) in the United States also suggested that there were no significant differences in children's inattention/restlessness by household type. Likewise, there were no statistically significant differences in terms of bully victimisation, substance use frequency, total delinquency score, conduct disorder or socialised aggression (Edwards, 2016;Robbins et al, 2006).…”
Section: Mentalmentioning
confidence: 99%
“…Along with fathers spending more time with their children, changes to family structure highlight the importance of considering the influence of all caregivers on child health and wellbeing. From 1960 to 2014, while the prevalence of children living in a home with two parents in their first marriage decreased (Pew Research Center, 2015), there was an increase of single female caregiver homes, blended families including stepparents and other relatives as primary caregivers, including grandparents (National Academies of Sciences, 2016;Pew Research Center, 2015;Rapoport et al, 2020). Furthermore, the Williams Institute on Sexual Orientation and Gender Identity Law and Public Policy analyzed pooled data from the 2008 and 2010 "General Social Survey," reporting that of adults who identified as lesbian, gay, or bisexual, 38% have had at least one child (Gates, 2012).…”
Section: Introductionmentioning
confidence: 99%